PENGARUH CITRA, KUALITAS PELAYANAN DAN FASILITAS TERHADAP LOYALITAS KONSUMEN YANG DIMODERASI KEPUASAN KONSUMEN (Studi Kasus Pada Lembaga Pendidikan Primagama Cabang Rembang) - Nurdiyansah, Didik; Dewi, Dian Ayu Liana (potensio, 2013)
This study aims to determine the effect of the image, quality of service and facilities to customer loyalty customer satisfaction moderated the educational institutions Primagama Apex branch. The study population was all students Primagama Apex in October 2011, which totaled 130 students. with a sample of 43 students. Data collection techniques in this study is through questionnaires and interviews. Analysis techniques used in this study is the technique of regression analysis using the variables moderating. From the calculation of the variable partial image, service quality and satisfaction moderated variable image positive and significant impact on loyalty, while variable facilities, service quality and satisfaction moderated variablefasilitas not moderated satisfaction and a significant positive effect on loyalty. Simultaneously acquired that image, quality of service, and facilities together are moderated customer satisfaction and a significant positive effect on loyalty in services products.Â Keywords: Image, Quality Service, Facilities, Customer Satisfaction, Loyalty Consumers.